APAKAH PROMOSI PENJUALAN MELALUI MEDIA SOSIAL DAN POTONGAN HARGA MEMENGARUHI NIAT BELI KONSUMEN DENGAN KENAIKAN TARIF PAJAK PENAMBAHAN NILAI SEBAGAI VARIABEL MODERASI? - Akmal Fikri Fadhiilah; Nurul Aisyah Rachmawati (Universitas Budi Luhur, 2024)
This research aims to test whether increasing Value Added Tax (VAT) rates, sales promotions via social media, and price discounts affect consumer purchasing intentions. This research also aims to test whether the increase in VAT rates weakens the positive relationship between sales promotions via social media and price discounts on consumer purchase intentions. This research uses primary data obtained through a survey method among students studying on campuses in the South Jakarta area. The data were analyzed using Partial Least Square. This research found that increases in VAT rates, sales promotions via social media, and price cuts positively affect consumer purchasing intentions. However, the increase in VAT rates cannot moderate the relationship between sales promotion via social media and price discounts on consumer purchase intentions. This research indicates that sales promotions via social media, price discounts, and increases in VAT rates can influence consumer behavior when purchasing a product. For sellers, this can be used as a company strategy to increase turnover.